1989
DOI: 10.1148/radiology.170.2.2911678
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution measured with CT: correlations in healthy subjects, patients with anorexia nervosa, and patients with Cushing syndrome.

Abstract: Computed tomography (CT) was used to study fat distribution in three groups of women of comparable age: 39 healthy volunteers, 15 patients with anorexia nervosa, and seven with Cushing syndrome. Patients with anorexia nervosa had a fivefold decrease in subcutaneous fat and only a twofold decrease in intraabdominal fat compared with the values for the volunteers. Patients with Cushing syndrome had less than a twofold increase in subcutaneous fat and greater than a fivefold increase in intraabdominal fat compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 0 publications
5
94
1
Order By: Relevance
“…128 Abdominal fat accumulation in CS has been attributed to the redistribution of peripheral fat to the visceral fat depot. 129,130 However, it is interesting to note that visceral fat accumulation in CS does not correlate with lipid and glucose profiles. 131 It is well established that glucocorticoid excess, as observed in CS, is associated with an adverse glucose and lipid profile that increases metabolic and cardiovascular risk.…”
Section: Glucocorticoid Excessmentioning
confidence: 99%
“…128 Abdominal fat accumulation in CS has been attributed to the redistribution of peripheral fat to the visceral fat depot. 129,130 However, it is interesting to note that visceral fat accumulation in CS does not correlate with lipid and glucose profiles. 131 It is well established that glucocorticoid excess, as observed in CS, is associated with an adverse glucose and lipid profile that increases metabolic and cardiovascular risk.…”
Section: Glucocorticoid Excessmentioning
confidence: 99%
“…Seeking to tackle serious methodological limitations of the early research, Thakore et al (2002) applied a wellvalidated technique of computed tomography (Mayo-Smith et al, 1989) to directly measure abdominal adiposity in a sample of drug-naive/free schizophrenic patients and ageand sex-matched healthy controls. They found that schizophrenic patients had higher body mass index (BMI) and over three times more abdominal fat , accumulation of which poses even greater cardiovascular/ diabetes risks than overall obesity .…”
Section: Weight Status Of Drug Naive/free Schizophrenic Patientsmentioning
confidence: 99%
“…Moreover, high rates of obesity and type II diabetes mellitus, observed in drug-naive/free patients (Mukherjee et al, 1996;Allison et al, 1999a;Thakore et al, 2002;Ryan et al, 2003Ryan et al, , 2004 before Kohen, 2004) and after the advent of antipsychotics and in nonschizophrenic blood relatives (Dynes, 1969;Mukherjee et al, 1989;Cheta et al, 1990;Martins et al, 2001;Lamberti et al, 2004), were potentially attributed to genetic factors (Stone et al, 2004), illness neurobiology (Thakore, 2005) and to unhealthy lifestyle (Brown et al, 1999). The interpretability of the preneuroleptic era data (reviewed in Kohen, 2004) is, however, limited by flaws in epidemiological methodology including lack of evaluation of and adjustments for adiposity, lifestyle, and anthropometric measures together with inconsistent diagnostic criteria for schizophrenia and glucose/insulin abnormalities Newcomer, 2005).Seeking to tackle serious methodological limitations of the early research, Thakore et al (2002) applied a wellvalidated technique of computed tomography (Mayo-Smith et al, 1989) to directly measure abdominal adiposity in a sample of drug-naive/free schizophrenic patients and ageand sex-matched healthy controls. They found that schizophrenic patients had higher body mass index (BMI) and over three times more abdominal fat , accumulation of which poses even greater cardiovascular/ diabetes risks than overall obesity .…”
mentioning
confidence: 99%
“…15 However, a single 3 mm CT scan slice through the level of the fourth lumbar vertebra still remains the best validated direct measure of visceral fat deposition as is reflected by a number of published studies which have used this technique to determine central obesity in patients suffering from certain general medical conditions 18,19 and psychiatric disorders. 22,23 To date, there has been no published study in the literature directly examining regional abdominal adiposity in patients with schizophrenia. Therefore, it was our intention in this study to measure abdominal fat distribution using CT scanning in patients with schizophrenia and compare them to normal controls.…”
Section: Introductionmentioning
confidence: 99%